Hubungan Antara Konsep Diri Dengan Prestasi Akademik Siswa Smp Negeri 1 Rawalo - Putri, Auliya Anisa; Sundari, Ririn Isma; Andini, Amelia (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2025)
Society and education need each other. Education helps individuals develop their potential, while society needs education to improve the quality of life. Education lasts from early childhood (PAUD) to college, forming individuals with mature skills and personalities. Adolescents, especially junior high school students aged 13–15, are going through an important transition period in their development. At this stage, they begin to build their identity and life principles. Adolescence is a transitional period for children, where during this period there will be many behaviors that reflect the development of self-concept, which can affect educational aspects including academic achievement. Students with a positive self-concept are more confident, open to criticism, and have realistic goals. Conversely, negative self-concept can hinder confidence and academic achievement. This study aims to determine the relationship between self-concept and academic achievement of SMP Negeri 1 Rawalo students. The research method is quantitative with a cross-sectional approach. The sample of this study was 154 respondents from grade 8 students at SMP Negeri 1 Rawalo which was taken using a simple random sampling technique. Data collection was carried out by distributing the Self-Concept questionnaire and the average ASAS score for semester 1. Data analysis uses spearman-rank test. The results showed a significant value of p value < 0.05 with a correlation coefficient value of r = 0.0182. The conclusion of this study is that there is a positive